Lessons Learned From Twenty-Eight Cases of Burns Following Breast Reconstruction: An Underestimated Complication Requiring Inclusion in Consent Information. (14th February 2021) - Habibi, Koohyar; Delay, Emmanuel; Sarfati, Isabelle; Duteille, Franck; Clough, Krishna B; Atlan, Michael
Abstract: Background: There has over recent years been a constant increase in annual breast reconstruction figures. Although reports indicate that burns following breast reconstruction are a rare occurrence, there has nevertheless been a relative increase in cases. The key underlying causes of this type of condition remain unknown. Objectives: The authors launched a new study on the demographic characteristics of burns in the breast reconstruction population with the inclusion of up-to-date data to assess cases and contributing factors. Methods: The study was a multicenter retrospective review of patients who underwent any type of breast reconstruction and subsequently sustained burn injuries. Results: Twenty-eight cases of burn injury following breast reconstruction were documented; 6 involved autologous flaps and 22 involved implants. Nine of the 10 implant exposure cases had previous history of radiotherapy, but there was no statistically significant difference between previous radiotherapy history and implant exposure ( P = 0.32). Of the 13 cases sustaining full-thickness burns, a large number included implant-based reconstruction (n = 12, 92%), although no statistically significant difference was observed between type of reconstruction and incidence of full-thickness burns ( P = 0.17). Conclusions: Each patient undergoing breast reconstruction should be advised of the potential risks and instructed to avoid significant heat exposure and steer clear of dark-colored bathing suits. At the time of writing, this information has yet to be included in the vast majority of surgery-related informed consent documents. Level of Evidence: 4: